Designing a patient‐specific search of transplant program performance and outcomes: Feedback from heart transplant candidates and recipients. Issue 2 (19th December 2020) - McKinney, Warren T.; Schaffhausen, Cory R.; Schladt, David; Bruin, Marylin J.; Chu, Sauman; Snyder, Jon J.; Martin, Cindy; Alexy, Tamas; Kasiske, Bertram; Israni, Ajay K.
Abstract: Background: The Scientific Registry of Transplant Recipients provides transplant program‐specific information, but it is unclear what patients and stakeholders need to know. Acceptance criteria for the candidate waitlist and donor organs vary by program and region, but there is no means to search for programs by the clinical profiles of recipients and donors. Methods: We examined variability in program‐specific characteristics that could influence access to transplantation. We also conducted three interviews and three focus groups with heart transplant candidates and recipients. Participants evaluated prototypes of a patient‐specific search tool and its capacity to identify programs tailored to specific patient needs. Patient experiences and feedback influenced the development of tools. Results: The distribution of recipient and donor characteristics influenced access to transplantation, as age and body mass index varied across programs (all with p  < .01). Several themes emerged related to decision‐making and the perceived usability of the patient‐specific search. Perceptions of the prototypes varied, but were positive overall and support making the patient‐specific search publicly available. Participants revealed barriers to evaluating transplant programs and suggest that patient‐specific search results may optimize the process. Conclusions: The patient‐specific tool (http://transplantcentersearch.org/ ) is valued by heart transplant patients and is important to maximizing access to transplant.